2009
DOI: 10.1056/nejmoa0900559
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Bypass Surgery with or without Surgical Ventricular Reconstruction

Abstract: BACKGROUND Surgical ventricular reconstruction is a specific procedure designed to reduce left ventricular volume in patients with heart failure caused by coronary artery disease. We conducted a trial to address the question of whether surgical ventricular reconstruction added to coronary-artery bypass grafting (CABG) would decrease the rate of death or hospitalization for cardiac causes, as compared with CABG alone. METHODS Between September 2002 and January 2006, a total of 1000 patients with an ejection f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
440
3
32

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 657 publications
(498 citation statements)
references
References 25 publications
9
440
3
32
Order By: Relevance
“…For patients with ischemic heart disease, SVR has yielded beneficial short-term effects on functional status, exercise performance, long-term results, and quality of life 48,49) . However, concomitant SVR is still controversial during CABG for these patients 48,49,50) . Recently, the Surgical Treatment for Ischemic Heart Failure (STICH) trial addressed this question and demonstrated that anatomical change by SVR was not associated with a greater improvement in symptoms or exercise tolerance or with a reduction in the rate of death or hospitalization for cardiac causes 50) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For patients with ischemic heart disease, SVR has yielded beneficial short-term effects on functional status, exercise performance, long-term results, and quality of life 48,49) . However, concomitant SVR is still controversial during CABG for these patients 48,49,50) . Recently, the Surgical Treatment for Ischemic Heart Failure (STICH) trial addressed this question and demonstrated that anatomical change by SVR was not associated with a greater improvement in symptoms or exercise tolerance or with a reduction in the rate of death or hospitalization for cardiac causes 50) .…”
Section: Discussionmentioning
confidence: 99%
“…However, concomitant SVR is still controversial during CABG for these patients 48,49,50) . Recently, the Surgical Treatment for Ischemic Heart Failure (STICH) trial addressed this question and demonstrated that anatomical change by SVR was not associated with a greater improvement in symptoms or exercise tolerance or with a reduction in the rate of death or hospitalization for cardiac causes 50) . Patient selection issues and hemodynamic effects of LV volume reduction have been proposed to explain these contradictory results 50) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a subgroup of 490 patients allocated to SVR in addition to CABG there was no benefit for the patients who had postoperative ESVI greater than 70 mL/m 2 . 141 These and other findings have generated much controversy and discussion.…”
Section: -151mentioning
confidence: 99%
“…Currently clinical trials are evaluating the effectiveness of percutaneous strategies to treat ventricular aneurysms [8,9]. The Surgical Treatment for Ischemic Heart Failure (STICH) trial was aimed to answer the role of ventricular restoration surgery with or without coronary revascularisation [10]. STICH reported no difference in outcomes for patients undergoing ventricular remodelling surgery.…”
Section: Introductionmentioning
confidence: 99%